Investigation of Interfacial Reaction Products and Stress Distribution in Selective Laser Melted Al12Si/SiC Composite Using Confocal Raman Microscopy - Li, X.; Kong, C.; Becker, Thomas; Sercombe, T. (2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, WeinheimThe interfacial reaction products and stress distribution in a selective laser melted Al12Si/SiC composite are studied using confocal Raman microscopy. Results reveal that needle-like Al4C3 and equiaxed Si are located at the interface between the Al matrix and SiC particles. This reaction is triggered by the high temperature within the SiC due to its high laser absorptivity. Raman frequency shifts to lower wavenumber are observed in both the SiC and Si, suggesting the existence of tensile stress within the interface. The tensile stress in SiC is higher in the build direction than in the direction perpendicular to the build direction. No such difference is observed in the Si. The reason is ascribed to the Gaussian distribution of the laser energy density and stress relief through the interfacial reaction.